Generation Z Awareness on Food Waste Issues (a Study in Tangerang, Indonesia) - Lemy, Diena Mutiara; Rahardja, Audrey; Kilya, Cynthia Swastika (Journal of Business on Hospitality and Tourism, 2020)
With resources becoming scarcer, waste of food is something to be avoided. Food waste must be minimized by using various ways to avoid waste in terms of food loss and food waste. In Indonesia itself, without realizing it, the issue of leftover food becomes very big. According to the Head of Representative of the United Nations Food Agency (FAO), Mark Smulders, of the approximately 1.3 trillion tons of food that was lost or wasted, Indonesia contributed around 13 million tons of food waste (food loss and food waste). This study will explore Generation Z's level of awareness of leftover food in Indonesia, especially in the Tangerang and surrounding areas. This research is exploratory in nature. The method is used to research something (which attracts attention) that is not yet known, not understood, or not well recognized. The date is collected using questionnaire that were distributed to respondents, namely Generation Z in Tangerang and its surrounding areas. From the results of data processing and tests carried out in this study, it can be concluded that the current awareness of Generation Z on the issue of leftover food must be raised, because the issue of leftover food itself is one of the issues of environmental preservation. The level of awareness of the issue of leftover food from Generation Z as the next generation must be increased, because only less than half of respondents are aware of this issue of leftovers.